The ‘Cold War’ Between the Charismatic Movements on the Institutional Churches. - Rugyendo, Medard (The Journal of the College of Humanities and Social Sciences Makerere University, 2011)
The paper exposes how the Charismatic movement has greatly influenced the traditional churches. It is misunderstood as a new’religion’. The paper points out that some of the leaders of the traditional churches have been influenced by charismatic movement in worship-which is the central part of any church. The youth have greatly embraced the movement. It is also pointed out that the there is a ‘cold’war between the charismatic and non-charismatic: those that have not conformed. It is recommended that there is a need of blended worship and adequate Biblical exposition on gifts and gifting; which is the source of the said cold war.